Abandoned land: A barrier for sustainable development of agriculture of the Republic of Moldova - Tamara Leah (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
According to the General Agricultural Census the agricultural area utilized in agriculture consist 1.941.400 ha. At the same time, abandoned agricultural area was 246.900 ha, of which 60.600 ha, or 24.5%, belonging firms and 186.300 ha, or 75.5% - individual persons. Neglected land is abandoned for several reasons. More and more lands are abandoned by people who go abroad. But those who remain in the country are not able to work, they are elderly, have no financial resources to support their own land. Abandonment of agricultural land is a problem for adjacent land owners. This contributes to long-term increase the vulnerability of soil and there is a source of spread the weeds and creating conditions of outbreaks of diseases and pests of agricultural plants. There are lands which it state is not determined from 1992-1994. It is not clear what level of degradation of these soils. In order to redress the situation is necessary to implement the measures on maintain and improve an efficient land management, at republican, regional and local level, based on land consolidation, land monitoring, implementation activities directed towards the land protection and sustainable development of agriculture in Moldova.
Keywords: Q01; Q15; Q24; 330; abandoned land; agriculture; soil degradation; sustainable development